Cardiac screening before returning to elite sport after SARS-CoV-2 infection - Hédon, C.; Schnell, F.; Sosner, P.; Chagué, F.; Schuster, I.; Julia, M.; Duparc, A.; Guy, J.-M.; Molinari, N.; Michaux, L.; Cransac, F.; Cade, S. (Archives of Cardiovascular Diseases, 2022)
Background: SARS-CoV-2 infection can induce cardiac damage. Therefore, in the absence of clear data, a cardiac evaluation was recommended for athletes before returning to play after recent SARS-CoV-2 infection. Aim: To assess the proportion of anomalies detected by this cardiac screening. Methods: We reviewed the medical files of elite athletes referred for cardiac evaluation before returning to play after a non-hospitalized SARS-CoV-2 infection (based on a positive polymerase chain reaction or antigen test) from March 2020 to July 2021 in 12 French centres. Results: A total of 554 elite athletes (professional or national level) were included (median age 22 years, 72.0% male). An electrocardiogram (ECG), echocardiogram and exercise test were performed in 551 (99.5%), 497 (89.7%) and 293 (52.9%) athletes, respectively. We found anomalies with a potential link with SARS-CoV-2 infection in four ECGs (0.7%), three echocardiograms (0.6%) and three exercise tests (1.0%). Cardiac magnetic resonance imaging was performed in 34 athletes (6.1%), mostly due to abnormal first-line examinations, and was abnormal in one (2.9%). The rates of those abnormalities were not higher among athletes with cardiac symptoms or more severe forms of non-hospitalized SARS-CoV-2 infection. Only one athlete had a possible SARS-CoV-2 myocarditis and sport was temporally contraindicated. None had a major cardiac event declared during the follow-up. Conclusion: The proportion of cardiac involvement after non-hospitalized forms of SARS-CoV-2 infection in athletes are very low. Systematic cardiac screening before returning to play seems to be unnecessary.